The Prevalence of Genu Varum and Genu Valgum in Overweight and Obese Patients: Assessing the Relationship between Body Mass Index and Knee Angular Deformities: Genu varum and genu valgum in obese patients - Soheilipour, Fahimeh; Pazouki, Abdolreza; Mazaherinezhad, Ali; Yagoubzadeh, Khatereh; Dadgostar, Haleh; Rouhani, Farzaneh (Acta Biomedica Atenei Parmensis, 2020)
Background: Recent studies have shown evidence of a relationship between overweight and obesity with skeletal abnormalities, especially angular knee disorders.Aim of the study: To reveal causal relationship between obesity and skeletal abnormalities.Methods: This study was performed on 280 overweight or obese patients (with BMI > 25kg/m2) who referred to Rasoul Akram hospital in Tehran between 2017 and 2018. Several non-radiographic methods including measuring Q angle, inter-malleoli distance and distance between two knees were used to determine genu varum and genu valgum.  BMI was also calculated by dividing the weight by the square of the height.Results: The prevalence of genu varumand genu valgum was 8.6% and 10.0% respectively. There was a significant adverse correlation between the Q angle and BMI. The mean BMI in patients with and without genu varum was 39.07 ± 6.41 kg/m2 and 42.1 ± 2.26 kg/m2, respectively, which was significantly lower in the genuvarum group (P = 0.008). Also, the mean BMI in patients with and without genu valgum was 43.39 ± 3.33 kg/m2 and 41.58 ± 4.61  kg/m2, respectively, which was significantly higher in the genuvalgum group (P = 0.044). Also, there was a direct correlation between BMI of patients with inter-malleoli distance and inverse correlation between BMI and two knees distance.Conclusion: There is a strong and significant relationship between incidence of obesity and genu valgum; therefore, the prevalence of this deformity in obese individuals is predictable. Also, the lower incidence of genu varum in obese people is predictable in our society.